2019
DOI: 10.1002/adma.201900192
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Therapy Promotes Tumor Infiltration and Antitumor Activity of CAR T Cells

Abstract: Chimeric antigen receptor (CAR)-redirected T lymphocytes (CAR T cells) show modest therapeutic efficacy in solid tumors. The desmoplastic structure of the tumor and the immunosuppressive tumor microenvironment usually account for the reduced efficacy of CAR T cells in solid tumors. Mild hyperthermia of the tumor reduces its compact structure and interstitial fluid pressure (IFP), increases blood perfusion, releases antigens and promotes the recruitment of endogenous immune cells. Therefore, the combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(251 citation statements)
references
References 36 publications
3
248
0
Order By: Relevance
“…In vivo FL imaging showed that the ICG FL signal was significantly attenuated after laser irradiation (660 and 808 nm), mainly due to the quenching of the ICG signal caused by laser irradiation. However, the FL signal of ICG recovered 3 h after laser irradiation, which might be due to an S/HSA/ICG‐mediated optical intervention that promoted vasodilation and reduced tumor compact structure, thereby promoting more S/HSA/ICG accumulation in tumors. Syne with laser irradiation did not significantly inhibit tumor growth.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo FL imaging showed that the ICG FL signal was significantly attenuated after laser irradiation (660 and 808 nm), mainly due to the quenching of the ICG signal caused by laser irradiation. However, the FL signal of ICG recovered 3 h after laser irradiation, which might be due to an S/HSA/ICG‐mediated optical intervention that promoted vasodilation and reduced tumor compact structure, thereby promoting more S/HSA/ICG accumulation in tumors. Syne with laser irradiation did not significantly inhibit tumor growth.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al proposed photothermal nanoparticles of poly(lactic‐ co ‐glycolic) acid (PLGA) loaded with indocyanine green (ICG), to precondition the solid tumor under the near‐infrared (NIR) light irradiation. [ 31 ] The mild hyperthermia of the tumor reduced its compact structure and interstitial fluid pressure (IFP), increased blood perfusion, released antigens, and promoted the recruitment of endogenous immune cells ( Figure A). These effects promoted the penetration and therapeutic index of CAR‐T cells in solid tumors (Figure 6B).…”
Section: Nanoparticles As a Potent Platform For Reprogramming Tumor‐amentioning
confidence: 99%
“…[ 28 ] In addition to their roles in the suppression of immune response and the inhibition of cytotoxic T cell proliferation, [ 29 ] these critical features of the TME allow tumors to actively escape T‐cell‐mediated tumor‐specific immunity, by activating negative regulatory pathways (checkpoints) such as programmed cell death protein‐1 (PD‐1). [ 30 ] Abnormal tumor vessels (leaky, tortuous, and dilated blood vessels) may also create a physiological barrier to CAR‐T cell trafficking and infiltration, [ 31 ] and facilitate immune evasion. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%
“…Table attempts to summarize the more combinatorial strategies explored so far by different investigators in achieving improve and long‐lasting therapeutic effects by combining PTT and immunotherapy.…”
Section: Evidence Of Nanoparticle‐mediated Photoimmunotherapy For Indmentioning
confidence: 99%